Advancing Cultural Knowledge: Experiential Learning International Graduate Study Training Programs in the Health and STEM Disciplines - Janelle Jung; Rosemary S. Caffarella (Adult Education Research Conference, 2010)
This paper, based on a review of the case studies of international experiential learning programs in the sciences and health sciences, discusses key characteristics of current programs in increasing cultural knowledge among graduate students in those fields, and proposes a set of guidelines for future program development.